IMPLEMENTASI BALANCED SCORECARD DALAM PENGUKURAN KINERJA MANAJEMEN RUMAH SAKIT - Suryani, Yulana Tri; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to find out and to evaluate the management performance of Dr. R SosodoroDjatikoesoemo Bojonegoro Local General Hospital by using the concept of Balanced Scorecard. This research isconducted by using qualitative method and the data analysis technique has been done by using qualitativedescriptive analysis techniques i.e. collecting, processing, and data presenting. The result of this research showsthat the measurement of the management performance of the hospital is inefficient in achieving the efficiency ofexpenditure because it does not balance with the level of income growth every years. It has been found from thelevel of patients satisfaction, it can be said it is already well, it has been proven by the result quality IKM and theresult of questionnaires. Furthermore, it states good in the process of innovation and its operating. There are alsomany training which are given to the medical and non-medical personnel in the learning process and there aremany facilities which give benefit in order to increase the infrastructure of the hospital. It has been found fromthe explanation above that Balanced Scorecard is considered to be good to become the standards in themeasurement of the management performance of the hospital.Keywords: Balanced Scorecard, Performance Measurement, Strategy